Boletaceae in China: Taxonomy and phylogeny reveal a new genus, two new species, and a new record - Wang, Yang; Wang, Li-Ying; Dai, Dan; Qi, Zheng-Xiang; Zhang, Zhen-Hao; Liu, Ya-Jie; Hu, Jia-Jun; Zhang, Peng; Li, Yu; Zhang, Bo (Frontiers in Microbiology, 2023)
Boletaceae, the largest family in Boletales, has been attracted by mycologists in the world due to its diverse morphology and complex history of evolution. Although considerable work has been done in the past decades, novel taxa are continually described. The current study aimed to introduce three new taxa and one new record of Boletaceae from China. The morphological descriptions, color photographs, phylogenetic trees to show the positions of the taxa, and comparisons with allied taxa are provided. The new genus Hemilanmaoa is unique in the Pulveroboletus group, and Hemilanmaoa retistipitatus was introduced as the type species. It can be distinguished by its bluing basidioma when injured, a decurrent hymenophore, a stipe covered with distinct reticulations, and a fertile stipitipellis. Porphyrellus pseudocyaneotinctus is characterized by its pileipellis consisting of broadly concatenated cells and thin-walled caulocystidia in Porphyrellus. In Phylloporus, Phylloporus biyangensis can be distinguished by its hymenophores that change to blue when injured and yellow basal mycelium. Lanmaoa angustispora, as a new record, is first reported in Northern China. Internal transcribed spacer (ITS), 28S rDNA (28S), translation elongation factor 1-alpha (tef1-α), RNA polymerase II subunit 1 (rpb1), and RNA polymerase II subunit 2 (rpb2) were employed to execute phylogenetic analyses.